(untitled) (International Journal of Scientific Trends, 2024)
One of the main pillars of music, besides rhythm, is the mode or sound row. Therefore, historically, the issue of sound rows has always been significant in music theory and practice. In the theoretical teachings and musical treatises of scholars from all eras, there are scientific views regarding the formation and creation of sound rows. Some of these scientific views differ from one another, while others are based on the same theoretical foundation.